Proximal humerus fixation failure for 3 parts proximal humeral fracture in plating and reverse total shoulder arthroplasty: A case report - Soehadak, Faizal Ariffianto; Gunawan, Vincent; Christianto, Rio Yudistira; Suroto, Heri (Edelweiss Applied Science and Technology, 2025)
Proximal humeral fracture (PHF), with an incidence rate of 266: 100.000 people, is a common and challenging fracture. Open reduction internal fixation (ORIF) is an option for managing it by using a proximal humeral plate or Reverse Total Shoulder Arthroplasty (RTSA) if shoulder arthroplasty is being considered. We report a 66-year-old male with a 3-part PHF initially treated with ORIF. Twenty-six months later, the patient developed non-union with humeral head osteonecrosis (HHO), leading to RTSA. After initial improvement, he presented 40 months post-RTSA with shoulder dysfunction following a massage. Imaging revealed implant failure. Revision surgery showed wear of the metaphyseal component and soft tissue metallosis. The component was replaced, and the tissue debrided. Postoperatively, the patient experienced mild pain with improved but limited shoulder motion. This case illustrates multiple complications in PHF management, including fixation failure and HHO due to lack of medial calcar support. Despite literature supporting RTSA over ORIF in older patients, implant design and bone loss remain significant factors for RTSA failure. Metallosis, although rare, may arise from component wear and should be considered in revision planning. In managing PHF, medial calcar support restoration should be done to minimize the risk of HHO, especially in elderly osteoporotic bone. When HHO occurs, osteosynthesis could be converted to RTSA. In the case of RTSA, further research is needed to minimize the risk of implant failure, reoperation, and especially metallosis because an extensive debridement can lead to instability.